Zograscopic Viewing. (May 2013) - Koenderink, Jan; Wijntjes, Maarten; van Doorn, Andrea
The "zograscope" is a "visual aid" (commonly known as "optical machine" in the 18th century) invented in the mid-18th century, and in general use until the early 20th century. It was intended to view single pictures (thus not stereographic pairs) with both eyes. The optics approximately eliminates the physiological cues (binocular disparity, vergence, accommodation, movement parallax, and image blur) that might indicate the flatness of the picture surface. The spatial structure of pictorial space is due to the remaining pictorial cues. As a consequence, many (or perhaps most) observers are aware of a heightened "plasticity" of the pictorial content for zograscopic as compared with natural viewing. We discuss the optics of the zograscope in some detail. Such an analysis is not available in the literature, whereas common "explanations" of the apparatus are evidently nonsensical. We constructed a zograscope, using modern parts, and present psychophysical data on its performance.